Desdimelita spicatimanus a new species of Melitidae Bousfield, 1973 (Crustacea: Amphipoda: Hadziida) from the Sea of Okhotsk - Labay, Vjacheslav S. (Zootaxa, 2022)
A new amphipod species, Desdimelita (?) spicatimanus sp. nov., from the north-eastern slope of the Sea of Okhotsk (Russian Far East) is described. The new species is tentatively assigned to the genus Desdimelita because it is similar to females of the species of this genus in most of the characters: in the structure of the mouthparts, the armament of the dactylus of pereopod 2 (gnathopod 2), the anterior and posterior margins of the propodus of pereopods 1 and 2 (gnathopods 1 and 2), pereopods 3–7, uropods and telson. The new species differs from other Desdimelita species by the morphology of propodus of pereopod 2: broadened; palm with a row of 5–6 rare strong long robust setae). It also differs from D. microphthalma Jarrett & Bousfield, 1996 in larger eyes; from D. barnardi Jarrett & Bousfield, 1996 and D. transmelita Jarrett & Bousfield, 1996 it differs by the presence of a postero-dorsal tooth (teeth) on urosome 1; from D. californica (Alderman, 1936) it differs by the presence only a single postero-dorsal tooth on urosome 1; from D. desdichada (J.L. Barnard, 1962) and D. microdentata Jarrett & Bousfield, 1996 it differs by the long dactylus of pereopods 5–7. Keys to the world species of the genus Desdimelita is provided.